2023
DOI: 10.1158/1078-0432.ccr-22-2462
|View full text |Cite
|
Sign up to set email alerts
|

Endoglin, a Novel Biomarker and Therapeutical Target to Prevent Malignant Peripheral Nerve Sheath Tumor Growth and Metastasis

Abstract: Purpose: Malignant peripheral nerve sheath tumors (MPNSTs) are highly aggressive soft-tissue sarcomas that lack effective treatments, underscoring the urgent need to uncover novel mediators of MPNST pathogenesis that may serve as potential therapeutic targets. Tumor angiogenesis is considered a critical event in MPNST transformation and progression. Here, we have investigated whether endoglin (ENG), a TGF-β coreceptor with a crucial role in angiogenesis, could be a novel therapeutic target in MPNSTs. Experimen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Unfortunately, the phase 3 trial evaluating TRC105 in combination with Votrient (pazopanib)-a small molecule multikinase inhibitor that primarily inhibits VEGFRs, did not show greater benefit in patients with advanced or metastatic angiosarcoma [58]. A recent xenograft study showed that combination treatments with TRC105 and PD901 (anti-MEK) inhibited soft-tissue sarcomas and concluded ENG would be a promising therapeutic target [59]. Since targeting MerTK in TNBC with different inhibitors has shown promising results [21], evaluating therapeutic strategies simultaneously targeting MerTK and ENG may be a promising avenue for the treatment of TNBC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the phase 3 trial evaluating TRC105 in combination with Votrient (pazopanib)-a small molecule multikinase inhibitor that primarily inhibits VEGFRs, did not show greater benefit in patients with advanced or metastatic angiosarcoma [58]. A recent xenograft study showed that combination treatments with TRC105 and PD901 (anti-MEK) inhibited soft-tissue sarcomas and concluded ENG would be a promising therapeutic target [59]. Since targeting MerTK in TNBC with different inhibitors has shown promising results [21], evaluating therapeutic strategies simultaneously targeting MerTK and ENG may be a promising avenue for the treatment of TNBC patients.…”
Section: Discussionmentioning
confidence: 99%